Mobile Authentication with NFC enabled Smartphones - Kilani, Rawad; Jensen, Kenneth (Technical Report Electronics and Computer Engineering, 2013)
Smartphones are becoming increasingly more deployed and as such new possibilities for utilizing the smartphones many capabilities for public and private use are arising. This project will investigate the possibility of using smartphones as a platform for authentication and access control, using near field communication (NFC). To achieve the necessary security for authentication and access control purposes, cryptographic concepts such as public keys, challenge-response and digital signatures are used. To focus the investigation a case study is performed based on the authentication and access control needs of an educational institutions student ID. To gain a more practical understanding of the challenges mobile authentication encounters, a prototype has successfully been developed on the basis of the investigation. The case study performed in this project argues that NFC as a standalone technology is not yet mature to support the advanced communication required by this case. However, combining NFC with other communication technologies such as Bluetooth has proven to be effective. As a result, a general evaluation has been performed on several aspects of the prototype, such as cost-effectiveness, usability, performance and security to evaluate the viability of mobile authentication.